Phytoplankton-bacteria relationship in the Antarctic marine ecosystem - Billen, Gilles; Becquevort, Sylvie (Polar Research, 1991)
Keywords: Sørishavet; Weddellhavet; bakterier; biomasse; fytoplankton; marin biologi; oseanografi; økofysiologi; økosystemer

The Crary Fan: A trough-mouth fan on the Weddell Sea continental margin, Antarctica - Kuvaas, Berit; Kristoffersen, Yngve (Marine Geology, 1991)
Multichannel seismic investigations show the presence of a large trough-mouth fan deposit on the continental margin in the southern Weddell Sea. A characteristic feature of the fan is relatively few, but large canyons and/or channels which appear to have been stable for long periods. Levees associated with the channels may reach thicknesses of more than 1 km. Drilling during ODP Leg 113 recorded the presence of glaciers in East Antarctica since early Oligocene time, and the seismic stratigraphic evidence suggests that the submarine fan is largely composed of glacigenic sediments. The channel-levee systems and complexes indicate several growth phases, apparently controlled by glacial/interglacial climate fluctuations, with maximum fan growth during glacial periods. The present interglacial period is characterized by strong and erosive flow of Ice Shelf Water running down the western slope of the fan and carrying only minor amounts of suspended matter. The fan is essentially sediment starved during interglacial periods. The dimensions of the channel-levee complexes and the persistent loci of sediment supply suggest that turbidite sedimentation resulted from melting of wet-based glaciers at or near the shelf edge, which has consequently prograded 70-80 km seaward.
Keywords: Sørishavet; Weddellhavet; havbunnen; isshelf; kontinentalmargin; kontinentalsokkel; marin geologi; seismologi

Microbial communities from the sea ice and adjacent water column at the time of ice melting in the northwestern part of the Weddell Sea - Mathot, Sylvie; Becquevort, Sylvie; Lancelot, Christiane (Polar Research, 1991)
Keywords: Sørishavet; Weddellhavet; alger; bakterier; diatomeer; havis; mikrobiologi; protozo; sjøis; smelting